Analysis of Business Income of Laying Chicken Breeders UD. Unggas Mandiri in Konda District, South Konawe Regency (Pascasarjana Universitas Sulawesi Tenggara, 2022)
This study aims to determine the business income of laying hens breeders UD. Unggas Mandiri, Konda District, South Konawe Regency. This research was conducted from July to August at UD. Unggas Mandiri, Konda District, South Konawe Regency. The research location was determined purposively (purposive sampling) on the consideration that the location contained laying hens which had a relatively large population. Respondents in this study were business owners and employees of UD. Unggas Mandiri, Konda District, South Konawe Regency. The results showed that the income earned in the UD. Unggas Mandiri, Konda District, South Konawe Regency, which has an income of 465,385,185 per period. Laying chicken farming business UD. Unggas Mandiri, Konda District, South Konawe Regency is feasible to run based on the R/C Ratio value of 1.17 and the B/C Ratio value of 0.17.